1961
DOI: 10.1002/cjce.5450390504
|View full text |Cite
|
Sign up to set email alerts
|

Optimum performance of combined flow reactors under adiabatic conditions

Abstract: Irrevereible first-and eieeond-order reactions are studied for combinations of tubular and CST reactors when endothermal or exothermal adiabatic conditions prevail.Typical results presented for itf T and, Tr)i models show the variation of either the conversion or the relative residence time as a function of the mixing level of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Cholette and Blanchet (9) were probably the first to study series reactor combinations under adiabatic operating conditions. They found that for isothermal and endothermic reactions the plug flow reactor always gives a greater conversion than a series combina tion of the CSTR and plug flow reactor.…”
Section: Purposementioning
confidence: 99%
“…Cholette and Blanchet (9) were probably the first to study series reactor combinations under adiabatic operating conditions. They found that for isothermal and endothermic reactions the plug flow reactor always gives a greater conversion than a series combina tion of the CSTR and plug flow reactor.…”
Section: Purposementioning
confidence: 99%
“…Combinations of PFR and CSTR for irreversible first and second order reactions under endothermic and exothermic adiabatic conditions also have been studied (Cholette and Blanchet, 1961). Aris (1961~) has optimized combination of reactors for simple reaction schemes using dynamic programming.…”
Section: Introductionmentioning
confidence: 99%
“…Aris (l) quantitatively demonstrated a basis for selection of the combination to use for maximum conversion. As a single adiabatic reaction unit, Cholette and Blanchet (6) showed that for an endothermic reaction, the same situation existed as for an isothermal system in that a tubular reactor was superior. For an exothermic reaction, the choice of which reactor is superior is dependent upon the conversion range under consideration.…”
Section: Studies Of Adiabatic Reactors Have Been Made In Analogous Simentioning
confidence: 98%
“…Cholette and Blanchet (6) considered series combinations of tubular and mixed tank reactors. For exothermic reactions, a combination of types resulted in greater con version than either type of reactor alone.…”
Section: Studies Of Adiabatic Reactors Have Been Made In Analogous Simentioning
confidence: 99%